Non-connected pores of the Longmaxi shale in southern Sichuan Basin of China. (December 2019) - Fu, Yonghong; Jiang, Yuqiang; Wang, Zhanlei; Hu, Qinhong; Xie, Jun; Ni, Gensheng; Lei, Zhian; Zhou, Keming; Liu, Xiongwei
Abstract: The characteristics of non-connected pores of four Longmaxi shale samples from the southern Sichuan Basin of China were investigated from the studies of pore size distribution (PSD), pore volumes, pore types using helium pycnometry [gas injection porosimetry (GIP) and GRI (Gas Research Institute) method], nuclear magnetic resonance (NMR), nuclear magnetic resonance cryoporometry (NMRc), and spontaneous water and oil imbibition experiments. GRI porosity on particle sizes less than 5 mm sample and a 2 MPa helium injection pressure provides information on the total porosity, including both non-connected and connected pores. GIP porosity using core plugs only measures connected pores which extend to the surface of the sample accessible by helium. So the difference between GRI and GIP porosities is used to estimate the volumes of non-connected pores. And the volumes of non-connected pores accounts for 17.5%–40.3% of the total pore volume. For NMRc test results, total pore volume increases with sample size decrease, and the great difference of pore volume with a pore diameter range from 5 nm to 31 nm between small cylinder sample and 0.15–0.075 mm crushed sample is caused by non-connected pores opened. With a decrease of length for cubic samples, the increase in volume and rate of oil imbibition is greater than that of water imbibition, indicating that the non-connected pores are considered to be mainly oil-wet. In addition, the percentage of non-connected pores has a good correlation with TOC (total organic carbon) content. Therefore, this evidence implies that non-connected pores are mainly within the organic matter. NMR tests at different drying temperatures and a NMRc experiment provide a quantitative classification of the shale pore system which indicates that the exploitable pore diameters are larger than 4.25 nm. So non-connected pores with a diameter of 5–31 nm could be effectively exploited if connected by fracturing. The more the non-connected pores are opened, the better the pore connectivity of shale reservoir will be, with a less possibility of water blocking. In the process of shale gas development, attention should be paid to the interaction between fracturing fluid and rock components in order to release more non-connected pores. Therefore, to increase shale gas extraction efficiency, more effort should be directed towards identifying natural, and creating induced, porosity. Highlights: Non-connected pore fractions of the studied shale are obtained from complementary approaches. The shale pore system was quantified using NMR and NMRc methods, with measurable pore diameters down to 4.25 nm. Non-connected pores, which are mainly in organic matter, constitute 17–40% of total pore volume and have diameters of 5~31 nm.